AB0943 Monocyte/Neutrophil (M/N) CD64 Ratio is Useful for Differentiating Infection from Disease Activity in Systemic Lupus Erythematosus (SLE) Patients. (10th June 2014) - Kikuchi-Taura, A.; Tsuji, S.; Ohshima, S.; Yura, A.; Katayama, M.; Watanabe, A.; Teshigawara, S.; Yoshimura, M.; Kudo-Tanaka, E.; Harada, Y.; Katada, Y.; Matsushita, M.; et al.
Abstract : Background: Clinical decision-making in the management of fever is difficult when distinguishing infection and high disease activity in SLE. CD64 (FcγRI) is upregulated on monocytes as a response to interferon (IFN)-α in SLE 1 . In infection, upregulation of CD64 expression on neutrophils occurs with IFN-γ, granulocyte colony stimulating factor, or lipopolysaccharide. CD64 on neutrophils is known to be a sensitive and specific marker for detection of infection in rheumatoid arthritis patients (using a cutoff value of 2000 molecules per cell) 2 . Objectives: We examined the utility of quantitative CD64 molecules expressed on monocytes and neutrophils, and calculated mCD64/nCD64 ratio as a marker for distinction between infection and disease activity in SLE. Methods: In this study, 12 SLE patients with infections (iSLE), 10 SLE patients with high disease activity, (aSLE) (SLEDAI 12.1±7) and 20 healthy controls (HC) were enrolled. The expression level of CD64 per monocyte and neutrophil quantitatively were measured by flow cytometry, and the mCD64/nCD64 ratio were calculated. Comparisons of levels within each group were analyzed, and levels of respective measurements at both pre- and post-treatment were analyzed. Results: Results of mCD64, nCD64 and m/nCD64 ratio are presented in Table1 . The nCD64 value of iSLE and aSLE was 2000 molecules/cell or more together. There was no difference in mCD64 of iSLE and aSLE. m/nCD64 ratio was significantly lower among iSLE than in those without infection, aSLE, or healthy controls (p<0.001). After each treatment, the value of mCD64 and nCD64 were significantly decreased in iSLE and aSLE. But there was no change in mCD64/nCD64 ratio in aSLE, on the other hand it was increased in iSLE (p<0.01). Conclusions: A cutoff value of 2000 molecules per cell on neutrophils did not clearly distinguish infection from exacerbation in SLE. However, our results suggest that calculating m/n CD64 ratio can be useful to distinguish infection or disease activity in SLE. Moreover, combined mCD64 and nCD64 could help to guide therapeutic decision in SLE. References: Li, Y. et al. Arthritis Research & Therapy 2010, 12:R90. Matsui, T. et al. The Journal of Rheumatology 2006; 33: 2416-24. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2779